1995
DOI: 10.1364/ao.34.006287
|View full text |Cite
|
Sign up to set email alerts
|

Planar laser-induced-fluorescence imaging measurements of OH and hydrocarbon fuel fragments in high-pressure spray-flame combustion

Abstract: Planar laser-induced fluorescence images of OH have been obtained in liquid-fueled spray flames burning heptane, ethanol, and methanol over a range of pressures from 0.1 to 1.0 MPa. In addition to the OH fluorescence, a nonresonant fluorescence interference that increased rapidly with pressure was detected. Examination of the spectrum of this interference indicates that it arises from hydrocarbon fuel-fragment species in the fuel-rich zones of the flame. The pressure dependence of the fluorescence signal is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 21 publications
0
30
1
Order By: Relevance
“…The combination of these two effects causes the OH concentration (and hence OH PLIF signal) to closely mark the reaction zone in high-pressure diffusion flames, with a large signal differential from the flame zone to the surrounding gas. This has recently been demonstrated by Allen et al [17] who found the OH signal from the diffusion-flame zone of a steady spray flame to become progressively thinner as pressure was increased from 1 to 9.5 bar. At diesel conditions, where pressures are 50 bar or higher, the effect should be even more dramatic, and OH PLIF is expected to closely mark the diffusion flame zones.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The combination of these two effects causes the OH concentration (and hence OH PLIF signal) to closely mark the reaction zone in high-pressure diffusion flames, with a large signal differential from the flame zone to the surrounding gas. This has recently been demonstrated by Allen et al [17] who found the OH signal from the diffusion-flame zone of a steady spray flame to become progressively thinner as pressure was increased from 1 to 9.5 bar. At diesel conditions, where pressures are 50 bar or higher, the effect should be even more dramatic, and OH PLIF is expected to closely mark the diffusion flame zones.…”
Section: Introductionmentioning
confidence: 55%
“…This rate is slow at atmospheric pressure, and OH often persists well away from the flame front making it a less useful marker of the reaction zone [3,5,10,13]. However, as ambient pressure is increased, the super-equilibrium OH concentrations in the flame zone are more rapidly reduced to the equilibrium levels outside the flame zone [12,17]. Furthermore, for diffusion flames, the equilibrium level itself falls rapidly outside of the flame zone [13].…”
Section: Introductionmentioning
confidence: 99%
“…the attenuation of the laser sheet and fluorescence trapping, the thermal population of the level probed, the loss of population in the excited state by quenching and internal conversion and the collection efficiency of the detection system [21]. The crank angle dependent fluorescence of the seeded CH 2 O provides the pressure-and temperature-dependence of the LIF intensity (in air).…”
Section: Methods Of Quantificationmentioning
confidence: 99%
“…The molecular structures of these fuels are shown in Table 1 . By measuring the spatial locations of the PAH fluorescence signals and the evolution of PAHs [33][34][35][36][37][38][39][40][41] and through sampling investigations [42][43][44][45][46] , the evidences, linking the PAH fluorescence to the PAH molecules, have been shown in these literature studies. Through the present PAH-PLIF experiments, we aim to study the effects of molecular structure and hydroxyl functional group on the PAH formation and growth processes.…”
Section: Introductionmentioning
confidence: 99%